Green Energy and Environment - Hwa Yap, Eng; Huey Ping Tan, Andrew (IntechOpen, 2020)
Energy is a vital element in sustaining our modern society but the future of energy is volatile, uncertain, complex, and ambiguous; especially when facing a continuous drive to ensure a sustained and equitable access as well as mounting pressures to reduce its emissions. Traditional approaches in developing energy technologies have always been in isolation with distinct and unique contexts. However, we cannot afford to work in silos any longer. Future energy systems and their relationship with the society and the environment will have to be conceived, designed, developed, commissioned, and operated alongside and within contemporary geo-political, ethical, and socio-economic contexts. This has posed an unprecedented volatility, uncertainty, complexity, and ambiguity (VUCA), where systemic and holistic approaches are often warranted. This book aims to focus on the VUCA of addressing the future of energy and environment by considering contemporary issues and insights from diverse contexts, viewed as a system, and anchored upon emerging and smart energy technologies.